A PEMBERDAYAAN PEKARANGAN DENGAN BUDIDAYA TANAMAN OBAT DAN VERTIKULTUR - Mulyadi, Susanti Diana; Nurshanti, Fatma; Nurlaili, Nurlaili; Permata Sari, Fifian (Universitas Djuanda, 2022)
The yard is ground that surrounds the house, this ground has a multifunctional function, as a playground, place for social activities and place to grow various plants. The advantages of the yard as land for plant cultivation such as familial medicinal plants and vertical vegetable cultivation Land use for plant cultivation is very profitable. Crops are not only consumed by themselves, but also to increase the family income. This community service is performed in Lekis Rejo Village, Kec. Lubuk Raja OKU South Sumatera. This service aims to utilize the site and increase the income of the people. The service will be held in 13-28 February 2020 at Lekisrejo Village, OKU Regency. Method of devotion with lectures, questions and answers, and practice. The transfer of science and technology given to farmers groups in this service is to explain how technology can be used in the cultivation of medicinal plants and the vertical cultivation of vegetables. The steps that will be followed are 1. Cultivation of kencur, ginger and turmeric. 2. Vegetable growing vertically. These activities include: 1). Preparation of seeds, 2) preparation of land/planting media, 3) Planting, 4) Maintenance and 5) Harvesting. The output goals in this community service activity are improving the community's understanding and skills in medicinal plant growing and Verticulture